INFORMATION SERVICES TO INCREASE THE EFFECTIVENESS OF SELFCONCEPT AND DEVELOPMENT IN SMK STATE 3 PADANGSIDIMPUAN SCHOOL YEAR 2015-2016 - Nur Mita Ika Saputri (Universitas Muhammadiyah Tapanuli Selatan, 2016)
This study was an experimental study using information services. The purpose of this is to mengetahu penelitian peningkatan self-concept and development through information services. The subjects in this study were all students of class X SMK Clothing N.3 Padangsidimpuan Academic Year 2015-2016 which totaled 98 students. The sample used in this study is claster random sampling technique. Samples are drawn throughout the class XClothing-2 totaling 30 people. The result of this determination is determined by a researcher and teacher at the school tersebut. Metode BK in this research is quantitative method, while the data collection techniques by using a questionnaire that is given to the student experiment class 2 times by providing information services treated 3 times the meeting until all finished indicators discussed. Data analysis technique using computer assistance SPSS version 20. The results of the study in the experimental class before carried on treatment (pre-test) as much as in 2168, while after the treatment (posttest) into 2641. It can be concluded that the implementation of information services can increase self-concept and development